2015
DOI: 10.1108/ejm-04-2014-0232
|View full text |Cite
|
Sign up to set email alerts
|

The effect of construal level on time perceptions, confidence in judgements and future preferences

Abstract: Purpose – This paper aims to examine how activating an abstract versus concrete construal as a retrieval cue – prior to providing estimates but after exposure to the stimulus – affects retrospective duration estimates of a hedonic experience, the kind of experience one might wish to repeat. Recent research has examined the effect of construal mindsets on prospective time perceptions (Hans and Trope, 2013) as well as the prediction of future durations (Kanten, 2011; Siddiqui et al., 2014). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…In the light of the CLT, access and purchase are related and both can be influenced by the level of an individual's mental construction. The examples portrayed in this section, such as (a) the influence of peers (Zhao & Xie, ), (b) the level of confidence in the choice (Tsai & McGill, ) or (c) satisfaction evaluation based on remembered information (Vilches‐Montero & Spence, ) can facilitate the transposition of results founded in so‐called ‘traditional’ consumption to the collaborative consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of the CLT, access and purchase are related and both can be influenced by the level of an individual's mental construction. The examples portrayed in this section, such as (a) the influence of peers (Zhao & Xie, ), (b) the level of confidence in the choice (Tsai & McGill, ) or (c) satisfaction evaluation based on remembered information (Vilches‐Montero & Spence, ) can facilitate the transposition of results founded in so‐called ‘traditional’ consumption to the collaborative consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Vilches‐Montero and Spence () also analyzed experiment evaluations. One of the main results of his research was to show that the abstract levels raise the memory of how the individual enjoyed the experience that has passed.…”
Section: Clt and Consumer Behaviourmentioning
confidence: 99%
“…In both cases, when importance is attached to a future-oriented goal and the value of exercise, the exercise intention is closer to a high-level construal than a low-level construal. Recent empirical studies have shown that abstract (or high-level) construal had a more positive effect on future preferences than did the concrete mind-set condition (or low-level construal) (Vilches-Montero & Spence, 2015), and as the tendency to consider future consequences became salient at the abstract construal level, preference for utilitarian foods products also increased (van Beek, Handgraaf, & Antonides, 2017). Therefore, participants’ continuation intentions of success can be enhanced more efficiently by providing them with DSF (emphasizing desirability) compared to FSF (emphasizing feasibility).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars largely converge on the viewpoint that unpacking an enjoyable past hedonic experience into its constituent sub-activities amplifies consumers' retrospective affective evaluation (Cowley 2014, Van Boven and Epley 2003, Vilches-Montero 2015, Vilches-Montero and Spence 2015. Telling the story of an enjoyable past experience also enhances experience duration estimation (Vilches-Montero and Spence 2015) and the self (Chawdhary and Riley 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite Yang et al (2014), however, extant research on WOM influence on the storyteller remains predominantly western, in terms of its empirical findings, and except for Moore (2012Moore ( , 2015 and Vilches-Montero and Spence (2015), no research investigates explaining language. Meanwhile, in consumer research as in any other field, replications are one of the building blocks of the structures of knowledge.…”
Section: Introductionmentioning
confidence: 99%